(untitled) (The Insight, 2025)
Background: Elevated parathyroid hormone (iPTH) levels have been associated with adverse cardiovascular outcomes in hemodialysis patients. This study aims to explore the relationship between elevated iPTH levels and cardiac dysfunction, with a focus on left ventricular ejection fraction (LVEF), left ventricular hypertrophy (LVH), and other cardiovascular markers. Objectives: To explore the role of parathyroid hormone (PTH) as a potential risk factor for cardiac dysfunction in individuals undergoing hemodialysis. Methods & Material: A total of 215 hemodialysis patients were enrolled and categorized into elevated iPTH and normal iPTH groups. Demographic data, dialysis duration, biochemical markers, and cardiovascular parameters, including LVEF, LVH, B-type natriuretic peptide (BNP), and carotid intima-media thickness (CIMT), were assessed. Logistic regression and multivariate linear regression were used to evaluate the relationship between iPTH and cardiovascular outcomes. Result: The elevated iPTH group had significantly lower LVEF (50.1% vs. 56.4%, p<0.001), higher prevalence of LVH (70% vs. 48.2%, p=0.002), and elevated BNP and CIMT levels (p<0.001). Multivariate analysis revealed that iPTH levels were independently associated with reduced LVEF and increased cardiovascular risk (adjusted OR: 2.34, p=0.012). Serum calcium and phosphorus imbalances were also significant predictors of cardiovascular dysfunction. Conclusion: Elevated iPTH levels are significantly associated with adverse cardiovascular outcomes, including reduced LVEF, increased LVH, and elevated BNP and CIMT, in hemodialysis patients. These findings highlight the critical role of iPTH in cardiovascular pathology and suggest that controlling iPTH levels could improve cardiovascular health in this population.